Using Technology to Support Healthcare Access in the Northern Regions of Brazil – A Telemedicine-based Approach - Chiavegatto, Rafael; Braga, Rodrigo; Rodrigues, Ueliton; Moura, Ricardo; Santos, Evaldo; Ferreira, Willon; Rodrigues, Eriky (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2026.42468, 2026)
Background: Access to primary healthcare services remains uneven in Brazil, particularly in the North region, where geographic distance, low medical density, and logistical constraints limit access to basic healthcare for remote communities. Aims: This paper presents a research and development project that aims to support communication between healthcare professionals and residents of remote communities in the North of Brazil through the use of telemedicine resources. Method: We conducted field visits and technical assessments in North communities to identify infrastructural, connectivity, and logistical constraints. Based on this analysis, we define aspects such as healthcare workflows, usage scenarios, and a telemedicine solution architecture, including a portable booth and a supporting digital platform. Results: We specified modules for vital signs collection, real-time video-based consultations, automatic transcription of medical consultations, and summary generation to support medical anamnesis. It also includes mechanisms for data security and privacy, as well as support for speech recognition and translation in indigenous languages. Conclusion: The current state of the project establishes a technical baseline that enables the implementation and evaluation of remote examinations and telemedicine consultations in real-world settings.